2020
DOI: 10.18502/ijrm.v13i10.7771
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of licorice extract on ovarian morphology, oocyte maturation, and embryo development in PCOS-induced mice: An experimental study

Abstract: Background: Polycystic ovary syndrome (PCOS) is an oxidative state resulting in ovarian dysfunction. Licorice is one of the natural antioxidants used for the treatment of infertility. Objective: To evaluate the effect of licorice extract on ovarian morphology, oocyte maturation, and embryo development in PCOS-induced mice. Materials and Methods: thirty-two female NMIR mice were divided into four groups (n = 8/each): control group receiving no treatment (group I); PCOS group injected with estradiol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Also, both doses of thymoquinone could decrease the number of atretic follicles that sig-nificantly increased in PCOS rats. This result is in accordance with Shamsi et al, who reported that licorice extract had a significant decrease in the number of atretic follicles (Shamsi et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Also, both doses of thymoquinone could decrease the number of atretic follicles that sig-nificantly increased in PCOS rats. This result is in accordance with Shamsi et al, who reported that licorice extract had a significant decrease in the number of atretic follicles (Shamsi et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…e examined healthy or atretic follicles were defined based on their morphology and diameter as follows: (1) primordial follicles (PRIF), where oocyte closely surrounded by one layer of flat granulosa cells,(2) primary follicles (PF), where the growing oocyte is surrounded by one layer of cuboidal granulosa cells, (3) preantral follicles (PAF), where several layers of granulosa cells surround the oocyte with no cavity within, (4) antral follicles (AF), where the oocyte is surrounded by cumulus oophorus cells within the cavity of the antrum, forming, (5)cystic follicles (CF),and(6) CL. Accordingly [16,17], morphological changes for the evaluation and enumeration of follicles were applied to characterize the follicular atresia and pyknotic nuclei in the granulosa layers; as such, from the basement membrane of oocytes, particularly degeneration of the granulosa layer was apparent in abnormal oocytes.…”
Section: Histopathological Analysismentioning
confidence: 99%
“…Due to the presence of phytoestrogens with aromatase‐inducing and 17HSD‐inhibiting activities, licorice can reduce testosterone synthesis and therefore can be used to treat women with PCOS (Kaur et al., 2013 ). In addition, according to a study on PCOS‐induced mice, licorice extract was shown to improve ovarian morphology, oocyte maturation, and embryonic development in a dose‐dependent manner (100 to 150 mg kg −1 day −1 for 21 days) compared to the control group (Shamsi et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, according to a study on PCOS-induced mice, licorice extract was shown to improve ovarian morphology, oocyte maturation, and embryonic development in a dose-dependent manner (100 to 150 mg kg −1 day −1 for 21 days) compared to the control group (Shamsi et al, 2020).…”
Section: Glycyrrhiza Glabra (Licorice-liquorice)mentioning
confidence: 99%